Discovery Learning Model Assisted by Geogebra-based Napier Bones on Students’ Division Problem Solving Ability - Palupi, Salsa Risky Eka; Andrijati, Noening (Jurnal Pendidikan MIPA, 2024)
Problem-solving ability is a basis that students must have in the learning process. This research aims to analyze the influence of the Discovery Learning model with Geogebra-based Napier Bones on improving students' division problem-solving ability. The population in this study was fourth-grade students of SDN Gugus Diponegoro. Sampling was done using the cluster random sampling technique. The sample in this research was fourth-grade students of SDN 1 Kalen and SDN 2 Nglandeyan. This research was carried out using quantitative research methods with experimental research types. The research design used a Quasi-experimental design. Data collection in this research was carried out by test techniques. The data analysis techniques used were normality test, homogeneity test, independent t test, and N-gain. The result of the research showed that there was a difference in division problem-solving ability in the experimental class which is higher than the control class. Based on the independent sample t-test, the significance value obtained 0,038 < 0,05. The N-Gain results show that the value in the experimental class was 0.501, which is in the medium category, while the value of the control class was 0.235 in the low category. This research concludes that the Discovery Learning model with Geogebra-based Napier Bones media has a significant influence on students' division problem-solving abilities.         Keywords: discovery learning, geogebra-based napier bones, problem solving ability.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp223-235